2017
DOI: 10.1103/physrevb.95.235120
|View full text |Cite
|
Sign up to set email alerts
|

First-principles description of van der Waals bonded spin-polarized systems using the vdW-DF+ U method: Application to solid oxygen at low pressure

Abstract: The description of the molecular solid phase of O2, especially its ground-state antiferromagnetic insulating phase, is known to be quite unsatisfactory within the local and semilocal approximations conventionally used in the Kohn-Sham formalism of density functional theory (DFT). The recentlydeveloped van der Waals (vdW) density functionals, vdW-DF, that take into account nonlocal correlations have also shown subpar performance in this regard. The difficulty lies in the subtle balance between the vdW interacti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The GW calculations 27,28 predicted an insulator-metal transition at ~100 GPa (but a structural transition at 50 GPa). This value of U lr eff (~9.6 eV) is not too high for the GGA + vdW-D + U method if we compare other studies in which DFT + U in combination with van der Waals density functionals reported that U eff = 5 eV and U eff = 12 eV are needed for the prediction of the lattice parameters of the alpha phase of solid oxygen using the revPBE and optB86b exchanges, respectively 29 . At low pressure (below 20 GPa), all the DFT calculations underestimate all of the lattice parameters, especially the intermolecular distance d 1 .…”
Section: Resultsmentioning
confidence: 75%
“…The GW calculations 27,28 predicted an insulator-metal transition at ~100 GPa (but a structural transition at 50 GPa). This value of U lr eff (~9.6 eV) is not too high for the GGA + vdW-D + U method if we compare other studies in which DFT + U in combination with van der Waals density functionals reported that U eff = 5 eV and U eff = 12 eV are needed for the prediction of the lattice parameters of the alpha phase of solid oxygen using the revPBE and optB86b exchanges, respectively 29 . At low pressure (below 20 GPa), all the DFT calculations underestimate all of the lattice parameters, especially the intermolecular distance d 1 .…”
Section: Resultsmentioning
confidence: 75%
“…10 A competition was observed between the nonlocal van der Waals interaction and ferromagnetic and anti-ferromagnetic orders in solid oxygen. [22][23][24] Therefore, the interplay between the nonlocal van der Waals, which originates from the London dispersion, and local interactions, in our opinion, should be treated carefully to further improve the prediction of solid oxygen.…”
Section: The Impact Of the Hubbard Correction On Structural Predictio...mentioning
confidence: 99%